Model Aplikasi Penjadwalan Mata Pelajaran Berbasis Android (Studi Kasus SMP Negeri 2 Natar Lampung) - Muhammad Alvin Ath Thaariq; Yuli Asriningtias (Jurnal Informatika, 2024)
ffective and efficient scheduling of school subjects is essential, especially in schools with a large student population and limited teaching staff, such as SMP Negeri 2 Natar, Lampung. Manual scheduling often leads to conflicts and is time-consuming. This study aims to develop an Android-based application that automates subject scheduling to minimize conflicts and enhance teachers’ productivity. The methodology includes data collection through interviews and observations, followed by application development using the Waterfall method and the Shuffle algorithm. The system uses SQLite for offline data storage and Flutter for the user interface. Testing results show that the application can quickly and effectively create conflict-free schedules, making it easier for teachers to manage their schedules. In conclusion, the application successfully achieves its goal of simplifying the scheduling process and optimizing time management in schools.